Dynamic stem cell heterogeneity - Krieger, Teresa; Simons, Benjamin D. (Development (Cambridge), 2015)
Recent lineage-tracing studies based on inducible genetic labelling have emphasized a crucial role for stochasticity in the maintenance and regeneration of cycling adult tissues. These studies have revealed that stem cells are frequently lost through differentiation and that this is compensated for by the duplication of neighbours, leading to the consolidation of clonal diversity. Through the combination of long-term lineage-tracing assays with short-term in vivo live imaging, the cellular basis of this stochastic stem cell loss and replacement has begun to be resolved. With a focus on mammalian spermatogenesis, intestinal maintenance and the hair cycle, we review the role of dynamic heterogeneity in the regulation of adult stem cell populations.